Coercive Diplomacy: Camp David 2000 - Iriqat , Dalal (Dirasat: Human and Social Sciences, 2022)
July 2000 hosted the most significant talks at Camp David bringing the final status issues to the negotiating table. However, no deal was completed; moreover, since then, violence and instability have escalated in the region, with the arrival of President Donald Trump to the White House, the Palestinian/Israeli peace process had taken a dramatic shift mainly because of the decisions that the administration had adopted regarding the final status issues; and more specifically on Jerusalem and refugees, which were finalized with the so called Trump Peace to Prosperity Plan. This paper sheds light on the theory of Coercive Diplomacy and applies it into the Palestinian/Israeli negotiations taking the Camp David 2000 Peace talks as case study and then examining what was presented at those talks in relation to what is now being implemented by the current US administration which dared to translate previous threats into reality. Reviewing past literature and relying on a number of books and conducting interviews with prominent negotiators from the American, Palestinian and the Israeli sides who participated at those peace talks, the study tells the true story of Camp David, demonstrates Coercive Diplomacy in Practice as it illustrates how the third party mediators have strongly crossed their limits by abandoning their role as mediators and by wearing the hats of interveners, the paper also demonstrates how Trump’s arrangement to an extent considered what was discussed at Camp David.